A case of child death caused by intestinal volvulus following magnetic toy ingestion. Issue 3 (May 2015) - Olczak, Mieszko; Skrzypek, Ewa
Highlights A sudden death of an 8-year old boy with a history of bloody vomits and stomach ache occurred in the ER of one of Warsaw's hospitals. Forensic autopsy revealed presence of two magnetic spheres in the lumen of the intestines. The cause of death was intestinal volvulus caused by foreign objects (two magnetic spheres) ingestion. Most likely the magnetic objects were part of a popular toy.